Pheno-morphological studies of selected tree species in a tropical forest ecosystem - Gopakumar S (Department of Tree Physiology and Breeding, College of Forestry, 1994)
A pheno – morphological study was carried out in pattikad Range of Trichur Forest Division, Kerala. Two groups of ten species each, where each group represented the moist deciduous and the semi – evergreen tract, were used for the present investigations. The study was initiated in March 1993 and was continued for a calendar year upto February 1994. The study was pursued with the objectives of supplementing information on the different phonological cycles of the commonly found species of this forest area. Along with this, the important macromorphological features of these trees were noted. An attempt was also done to understand the tree architectural principles of these species. The pattering of the phonological events like flowering, fruiting, leaf fall and leaf flushing, no doubt, are partly under endogenous control. However, in general, the timing of these life cycle events were noticed to follow a climatic cue. The deciduous habit exhibited by the study species during the dry weather had an ecological significance, because it strongly helped the trees to tide over the moisture limiting summer months. Likewise, dry season flower and fruit production shown by the species might be a part of a much complex adaptive strategy developed by these species through the course of competitive evolution. Apart from these climatic triggers, there exists possibilities of several, other external stimuli, that might have favoured these important seasonal cycles. However, the cardinal factor effecting these events would be the climatic factors, through its direct and indirect influences on the physiological mechanisms of these woody plants. Regarding tree architecture, it was noted that all the species build up through a progressive duplication of their basic architectural units. This architectural metamorphosis continued from seedling stage upto the death of the tree. Branch production and initiation of sexuality were intermediate events. However, the free expression of the architecture was found drastically affected, possibly due to the different stresses that perennial woody species encounters in its long life span.